Methodology for the Implementation of an interoperability protocol between RFID - NFC, applied to the registration of vaccines for COVID-19 - Herrera, Lucas (2021)
In this context caused by COVID-19, there are many atypical conditions, one of them and the one that is causing the greatest concern is related to the vaccine, it is a concern on the part of governments to be able to acquire the largest number of vaccines, and a concern on the part of people to be vaccinated. The present of having a vaccine registry and knowing who has been vaccinated, in most countries physical vaccination cards are being delivered, which is essential to be able to carry them to be able to perform certain operations, one of them may be to be able to enter public places until you can travel to other countries, the methodology that is presented is related to having an RFID card where it can always be carried being safer and difficult to deteriorate due to its material, in the RFID device the basic data can be stored of the person as well as the data of the vaccines that he is supplying, the methodology also proposes the design of a mobile application using the NFS communication protocol, which can be connected directly with the RFID device for both reading and writing data. . The results show that the methodology can be applied and scaled according to the needs of each country, with this information a connection is achieved between different processes and thus achieve interoperability between these devices and many applications, using the same device and for the benefit of the population and those authorized in order to know the status of the people who have been vaccinated.